2009
DOI: 10.1002/sia.3112
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of nicotine and cotinine in dusted latent fingermarks of smokers by using hydrophobic silica particles and MS

Abstract: Sub-micron sized hydrophobic silica particles doped with carbon black have been employed with latent fingermarks on glass and metal surfaces to develop a simple method for detecting nicotine and cotinine using surface assisted laser desorption/ionisationtime of flight-mass spectrometry (SALDI-TOF-MS) in positive ion reflectron mode. Dusting of surfaces enables location of marks for conventional identification of details but the particles also act as a laser desorption/ionisation enhancing agent (LDI) equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 14 publications
2
43
0
Order By: Relevance
“…Thus the MS of the five non-smoker's fingermark transfers show m/z 163 values which are not significantly higher than m/z 163 peak values in the MS of uncontaminated nonsmoker's marks. The identity of the m/z 163 signal from smokers' fingermarks was confirmed as nicotine from its SALDI-TOF-MS-MS (CID) fragmentation pattern, in line with our reported observations [12]. We have previously shown that cotinine (FW 176), which is the major metabolite of nicotine, can be detected in the dusted latent fingermarks of a small number of smokers [12] and our transfer experiments indicate that we can also detect cotinine together with nicotine in the fingermarks of non-smokers after shaking hands with a smoker (spectra not shown).…”
Section: Nicotine Transfer Through Direct Contact and Indirect Contacsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus the MS of the five non-smoker's fingermark transfers show m/z 163 values which are not significantly higher than m/z 163 peak values in the MS of uncontaminated nonsmoker's marks. The identity of the m/z 163 signal from smokers' fingermarks was confirmed as nicotine from its SALDI-TOF-MS-MS (CID) fragmentation pattern, in line with our reported observations [12]. We have previously shown that cotinine (FW 176), which is the major metabolite of nicotine, can be detected in the dusted latent fingermarks of a small number of smokers [12] and our transfer experiments indicate that we can also detect cotinine together with nicotine in the fingermarks of non-smokers after shaking hands with a smoker (spectra not shown).…”
Section: Nicotine Transfer Through Direct Contact and Indirect Contacsupporting
confidence: 90%
“…To prove the identity of m/z 163, SALDI-TOF-MS-MS (using CID) was carried out and the resulting fragmentation pattern was compared with the corresponding pattern at m/z 163 from a nicotine standard solution. Both spectra were performed under identical conditions and as we have reported for the m/z 163 peak in smokers, produced identical patterns using the hydrophobic silica particles proving that nicotine is in the sample of extract [12].…”
Section: Tobacco Extractionmentioning
confidence: 96%
See 1 more Smart Citation
“…This allows the analysis of organic features of large, delicate and valuable (such as paintings or manuscripts), or wet biological samples [115] , without the need for subsampling. Secondary ion mass spectrometers are already available for work in air, in MALDI (matrix-assisted laser desorption ionization [116]) and DESI (desorption electrospray ionisation [117]) applications, neither of which have the possibility of the simultaneous complementary techniques giving quantification and depth sensitivity.…”
Section: Chemical Analysis With Ibamentioning
confidence: 99%
“…Recently, hydrophobic silica particles doped with carbon black have been employed for the analysis of latent fingermarks on glass and metal surfaces in order to develop a simple method for detecting nicotine and cotinine. 91 Watanabe et al have developed SALDI-MS using zinc oxide (ZnO) NPs with anisotropic shapes. 92 ZnO-SALDI is advantageous for post-source decay (PSD) analysis and produces a simple mass spectrum in the case of phospholipids.…”
Section: ·4 Metal Oxide and Other Materials Based Npsmentioning
confidence: 99%